Comparative evidence on the value relevance of IFRS-based accounting information in Germany and the UK - Elbakry, Ashraf E.; Nwachuksu, Jacinta C.; Abdou, Hussein A.; Elshandidy, Tamer (Elsevier, 2016)
This paper uses panel cointegration with a corresponding vector error correction model (VECM) to investigate the changes in the value relevance of accounting information before and after the mandatory adoption of IFRS in Germany and the UK under three different valuation models. First, a basic Ohlson model, where our results indicate that despite the value relevance of the book values of equity has declined, it has been replaced by the increasing prominence of earnings in both Germany and the UK after the switch to the IFRS. Second, a modified model, which shows that the incremental value relevance of both earnings and book values are considerably higher in the long term for firms in the UK than in Germany. Third, a simultaneous addition of accounting and macroeconomic variables in an extended model, which indicates a significant rise in the relative predictive power of the book value of equity in the UK compared with the more noticeable impact on the value relevance of earnings in Germany. Collectively, the results of these models indicate that: (i) the explanatory power of linear equity valuation models is higher in UK than in the Germany, (ii) a long-run Granger-causal relationship exists between accounting variables and share prices in common law countries like the UK. Nevertheless, the implications of our findings lie in the knowledge that the potential costs of switching to the IFRS is completely nullified within three years by the benefits arising from a reduction in information asymmetry and earning mismanagement among firms which are listed on the stock exchanges of both common law and code law-based EU countries.